On RPS Algorithm of Fractional (1+1)-Dimensional Biswas-Milovic Equation - Korpinar, Zeliha; İnç, Mustafa (Amer Scientific Publishers, 2018)
In this work, Residual power series algorithm is studied to obtain numerical solutions of fractional (1+1)dimensional Biswas-Milovic equation. The Residual power series method (RPSM) gets Maclaurin expansion of the solution. The solutions of present equation are computed in the shape of quickly convergent series with quickly calculable fundamentals by using mathematica software package. Explanation of the method is given graphical consequens and series solutions are made use of to represent our solution. The found consequens show that technique is a power and efficient method in conviction of solution for the fractional (1+1)-dimensional Biswas-Milovic equation.
Keywords: Residual Power Series Method; Fractional (1+1)-Dimensional Biswas-Milovic Equation; Series Solution